Effect of rickettsial toxin VapC on its eukaryotic host. - Gilles Audoly (Public Library of Science (PLoS), 2011)
Rickettsia are intracellular bacteria typically associated with arthropods that can be transmitted to humans by infected vectors. Rickettsia spp. can cause mild to severe human disease with a possible protection effect of corticosteroids when antibiotic treatments are initiated. We identified laterally transferred toxin-antitoxin (TA) genetic elements, including vapB/C, in several Rickettsia genomes and showed that they are functional in bacteria and eukaryotic cells. We also generated a plaque assay to monitor the formation of lytic plaques over time and demonstrated that chloramphenicol accelerates host cell lysis of vapB/C-containing Rickettsia. Whole-genome expression, TUNEL and FISH assays on the infected cells following exposure to the antibiotic revealed early apoptosis of host cells, which was linked to over-transcription of bacterial vapB/C operons and subsequent cytoplasmic VapC toxin release. VapC that is expressed in Escherichia coli and Saccharomyces cerevisiae or microinjected into mammalian cells is toxic through RNase activity and is prevented by dexamethasone. This study provides the first biological evidence that toxin-antitoxin elements act as pathogenic factors in bacterial host cells, confirming comparative genomic evidence of their role in bacterial pathogenicity. Our results suggest that early mortality following antibiotic treatment of some bacterial infections can be prevented by administration of dexamethasone.